Inhibiting ATP6V0D2 Aggravates Liver Ischemia-Reperfusion Injury by Promoting NLRP3 Activation via Impairing Autophagic Flux Independent of Notch1/Hes1. (30th March 2021) - Wang, Ziyi; Wang, Hao; Chen, Xuejiao; Han, Sheng; Zhu, Yulin; Wang, Hanhua; Cheng, Feng; Pu, Liyong
Abstract : At present, liver ischemia-reperfusion (IR) injury is still a great challenge for clinical liver partial resection and liver transplantation. The innate immunity regulated by liver macrophages orchestrates the cascade of IR inflammation and acts as a bridge. As a specific macrophage subunit of vacuolar ATPase, ATP6V0D2 (V-ATPase D2 subunit) has been shown to promote the formation of autophagolysosome in vitro. Our research fills a gap which has existed in the study of inflammatory stress about the V-ATPase subunit ATP6V0D2 in liver macrophages. We first found that the expression of specific ATP6V0D2 in liver macrophages was upregulated with the induction of inflammatory cascade after liver IR surgery, and knockdown of ATP6V0D2 resulted in increased secretion of proinflammatory factors and chemokines, which enhanced activation of NLRP3 and aggravation of liver injury. Further studies found that the exacerbated activation of NLRP3 was related to the autophagic flux regulated by ATP6V0D2. Knocking down ATP6V0D2 impaired the formation of autophagolysosome and aggravated liver IR injury through nonspecific V-ATPase activation independent of V-ATPase-Notchl-Hesl signal axis. In general, we illustrated that the expression of ATP6V0D2 in liver macrophages was upregulated after liver IR, and by gradually promoting the formation of autophagolysosomes to increase autophagy flux to limit the activation of liver inflammation, this regulation is independent of the Notch1-Hes1 signal axis.